Development of Rhyzopertha dominica (F.) (Coleoptera Bostrichidae) on durum wheat kernels and semolina - Lidia Limonta (Journal of Entomological and Acarological Research, 2011)
he time necessary to larvae of Rhyzopertha dominica to drill kernels with or without dusts (semolina or debris from adults), and the possibility of development on semolina were evaluated. T ests were carried out on durum wheat kernels (Triticum durum Desfontaines), debris deriving from rearing, and semolina. Development was observed also on 0.5 and 6 mm of semolina and of debris. T hirty replicates were carried out for each test. The number of first instar larvae, that successfully drill sound kernels within 10 days, was higher by adding semolina or debris. When only kernels were provided, the time needed to larvae to drill increased. Development and the number of emerging adults were not significantly influenced by the addition of semolina to the kernels. Larvae couldn’t develop on 0.5 mm, while an equal number of individuals completed the development to adult in 6 mm of semolina as in the tests with kernels. When development was on debris, a lower number of emerged adults was observed.